Analysis of The Level of Taxpay Compliance For Micro Small Medium Enterprises in Paying Tax in Labuan Bajo - ViviLorensia Hartini; Agus Wahyudi (Eastasouth Institute, 2023)
This study aims to analyze the level of taxpayer compliance for SMEs in paying taxes in Labuan Bajo. The research method used is a quantitative descriptive method. The population of this study was 200 MSME actors in Labuan Bajo and the data collection technique used in this study was distributing questionnaires to respondents. The method of data analysis was carried out using a total sample of 100 MSME taxpayer respondents. Then the respondents' answers could be developed using the three box method formula. The results showed that the compliance of MSME taxpayers in Labuan Bajo in complying with tax regulations reached an average of 72.79% and was included in the high category.